Subject matter knowledge of student teachers: how does it affect their ability to teach entrepreneurship - Lope Pihie, Zaidatol Akmaliah; Hamzah, Ramlah (Universiti Putra Malaysia Press, 1997)
This study investigated 64 UPM student teachers' academic performance and their perception of their ability to teach commerce and entrepreneurship topics in the living skills syllabus. The findings show that (1) there is a significant difference between academic programmes and academic performance of the respondents, (2) entry qualifications influence academic performance of the respondents, and (3) high academic performance results in high ability to teach accounting components. This study suggests that proper selection of vocational teacher trainees should be made to ensure better living skills teachers. Selection should be based on experience in teaching living skills and satisfactory academic achievement. To produce professional teachers, teachers' subject matter knowledge should be increased by enrolling in several related courses.